Evaluación de la reducción de uso de leña, para la producción de ladrillo de arcilla, provincias de Moyobamba y Rioja – 2011 - Lozada Cubas, Jessy (2012)
The Clay Brick of Production in the of San Martin region indirectly influences in indiscriminate felling of trees, which principal source of energy for the process of the burnt one is the firewood, resources that come from the areas of headers of watersheds by is high calorific level; generating negative impacts, that is manifested through the loss of the great diversity of flora and fauna, decrease of the groundwater source of supply of the creeks, and rivers, putting at risk the water supply water for human consumption, emission of gases such as NOx, SOx, and inadequate waste management or solid waste. In this regard, with the aim of reducing the of firewood as their main source of energy and promote the use of environmentally sustainable energy the Regional Directorate of Production San Martin since 2007, has begun a process of Environmental Adaptation of these brickmakers Mypes in implementation DS No. 019-97-ITINCI: Regulations of Environmental protection for the Development of Activities in the Manufacturing Industry. The present investigation sought to determine to what quantity the production of brick clay located in the Rioja and Moyobamba provinces decreased the use of wood as a source of energy for the burner brick, for it the raising of field information had to realize in a total 11 Productive Units (brickmakers) according to the statistical sample to then be compared and the difference from the base line developed by the Martin Regional Direction of the production. Of the field information obtained and processed it us demonstrate that a year 2011 the Productive Units - Brickyards of the high May (Moyobamba and Rioja Provinces) reduced the use of firewood as source of energy for burned of brick of clay in 18.25% with regard to the Base Line obtained the year 2009 what represents a reduction in volume of 1,167 m3, reduction in deforestation in a proportion of 10.72 hectares / month and 128 Hectares / year; as well as can be seen the increase in other sources in a 18.25%, as the mineral coal and husk of rice, because of the low cost and availability in the market, this shows us that have been gradually reducing deforestation in the San Martín Region .